Microsystems for Enhanced Control of Cell Behavior Fundamentals, Design and Manufacturing Strategies, Applications and Challenges - Díaz Lantada, Andrés; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This handbook focuses on the entire development process of biomedical microsystems that promote special interactions with cells. Fundamentals of cell biology and mechanobiology are described as necessary preparatory input for design tasks. Advanced design, simulation, and micro/nanomanufacturing resources, whose combined use enables the development of biomedical microsystems capable of interacting at a cellular level, are covered in depth. A detailed series of chapters is then devoted to applications based on microsystems that offer enhanced cellular control, including microfluidic devices for diagnosis and therapy, cell-based sensors and actuators (smart biodevices), microstructured prostheses for improvement of biocompatibility, microstructured and microtextured cell culture matrices for promotion of cell growth and differentiation, electrophoretic microsystems for study of cell mechanics, microstructured and microtextured biodevices for study of cell adhesion and dynamics, and biomimetic microsystems (including organs-on-chips), among others. Challenges relating to the development of reliable in vitro biomimetic microsystems, the design and manufacture of complex geometries, and biofabrication are also discussed.
Some introductory notes to cell behavior -- Brief introduction to the field of biomedical microsystems -- Brief introduction to bio-microsystems for interacting with cells -- Common bioengineering resources for interacting with cells -- Methodologies for the development of bio-microsystems -- Addressing the complexity of biomaterials by biomimetic CAD -- Multi-scale and multi-physical/biochemical modeling in bio-MEMS -- Rapid prototyping of bio-MEMS for interacting with cells -- Nanomanufacturing for biomedical MEMS -- Issues linked to the mass-production of biomedical microsystems -- Biomedical microsystems for disease management -- Overview of microsystems for studying cell behavior under culture -- Microsystems for studying cell adhesion, dynamics and and overall mechanobiology -- Smart microsystems for active cell culture toward relevant tissues -- Tissue engineering scaffolds for 3D cell culture -- Tissue engineering scaffolds for bone repair: General aspects -- Tissue engineering scaffolds for bone repair: Dental repair -- Tissue engineering scaffolds for repairing soft tissues -- Tissue engineering scaffolds for osteochondral repair -- From labs-on-chips to microfluidic cell culture -- Cell-based sensors and cell-based actuators -- Towards reliable organs-on-chips and humans-on-chips -- Towards effective and efficient biofabrication technologies -- Project-based learning in the field of biomedical microsystems -- Annexes.
Keywords: Biomedical engineering; Biomaterials; Cytology; Microtechnology; Microelectromechanical systems; Biomedical Engineering and Bioengineering; Biomaterials; Cell Biology; Microsystems and MEMS